CORAL REEF CONSERVATION USING CORAL GARDEN INITIATIVE IN SEMPU ISLAND - oktiyas muzaky Luthfi (Journal of Innovation and Applied Technology, 2016)
Tambak Rejo is village in south of Malang has two hamlets there were Dusun Tambak Rejo and Dusun Sendang Biru. This village under Kecamatan Sumbermanjing Wetan which has coast line for 85.92 km. Sendang Biru became center of fisheries activities due to directly facing of Hindian Ocean that rich with pelagic fish such as tuna, tongkol and lobster. In this village there was a Nusantara fisheris landing port that allowed vehicle more than 30 GT lean. 500 m in front Sendang Biru laid a Sempu Natur Preserve that still has origin flora and fauna inside. The red color land in Sendang Biru has proved that this area rich on Fe and Al also many natural carst can be found easely. The aim of this program were to build coral garden in Sempu Island water and to educate community the importance of coral. Coral garden used steel frame with doom and pyramid shape. Coral will have transplanted and tied into frame until growth well. The donor coral was Acropora sp (representative of branching coral), Goniastrea aspera (massive coral) and Leptoseris yabei (foliose coral). We used participatory rural appraisal (PRA) to envolve communities in this program.